Cidade e Arquitetura na América Latina em três tempose alguns corolários norte-americanos 1492-1880-1929 - Pedro Henrique Almeida de Morais (2014)
This dissertation addresses the changes ocurred in Latin American cities and architecture in three historical moments of ruptures and striking transitions, which brought about profound changes in the reality of the American continent, fundamental to the basic understanding of the constitution of the countries of the region and therefore their cities and their architecture, central points of interest in this study. Prior to the treatment of the three key moments of the study, Chapter 1 seeks to clarify the starting point that led to the present work, the chosen mode of approach and the reasons and justifications for the trimming and timeline adopted. The second chapter seeks to establish some conceptual foundations that underlie the whole work, briefly pointing the historiographical approach taken, adressing the theme of influence as a relevant issue in the Latin American architecture, states a position over the historical changes treated on the research and tries to clear some relevant concepts on the subject of modernity. The first moment addressed is marked by the year 1492, the date of arrival of the first European settlers to America, an event that breaks with the relative continuity and full autonomy of activities that existing populations in America and particularly Latin America had prior to that event. The second main part takes as reference the year 1880, at which the reflections promoted by the European industrialization seem to finally be consolidated in Latin America more than a century after the beginning of industrialization in England aiming to understand how and what exactly were the consequences of this break in America, from the understanding of the gradual domination of Portugal and Spain by the powers of France and England, reflecting a new form of colonialism that encompass Latin America. The third and final moment addressed starts at the year of 1929, date from which a new change on a global scale points out the need for reconstruction of autonomy lost four centuries before, leading Latin American nations to seek and define their national identities - largely through art and architecture and whose developments are still in progress, strongly in the growth of cities and architectural production developed since then.